Response of broilers to digestible sulfur amino acids and threonine intake: Maximum economic return - Reis, Matheus De-Paula [UNESP]; Cunha-Melaré, Mirella [UNESP]; Silva-Viana, Gabriel; Zanardo-Donato, Daniella C. [UNESP]; Kazue-Sakomura, Nilva [UNESP] (Universidad de Antioquia, 2020)
Background: The determination of amino acid supplements for broiler chicken requirements based on performance does not always reflect maximum profitability. Objective: To estimate the optimal levels of digestible threonine (Thr) and sulfur amino acids (SAA) in diets for broilers based on an economic analysis. Methods: Two dose-response assays were conducted, and each assay was divided into three phases: initial (1-14 days), grower (15-28 days), and finisher (29-42 days). Five hundred and sixty male Cobb 500® broilers were randomly distributed to seven treatments with increasing levels of the amino acid (SAA or Thr), with four replicates and 20 birds each. Bodyweight gain (BWG) and feed intake (FI) were used to fit a segmented model. Gross income (GI), total feed costs (TFC) and gross margin (GM) were calculated based on local values. Results: Increasing levels of amino acid elicited a response in BWG and FI for all evaluated phases. The estimates for maximum profit based on GI and TFC were 223, 504, and 975 mg SAA/bird/d, and 236, 696, and 1,042 mg Thr/bird/d in starter, grower and finisher phases, respectively. Conclusion: Varying the AA prices affected only slightly the economic optimal intake of Thr and sulfur amino acids. Despite market fluctuations, the economic approach presented in this study demonstrates to be a helpful tool to choose the ideal inclusion level of amino acids in the feed.
Respuesta de pollos de engorde a la ingesta de aminoácidos azufrados y treonina digestibles: Máximo retorno económico
Resposta de frangos de corte ao consumo de aminoácidos sulfurados e treonina digestíveis: Máximo retorno econômico
Keywords: Amino acid supplementation; Dose-response; Economic return; Feed cost; Gross margin; Growth performance; Poultry; Segmented model